Glutathione-S-Transferase Variants are not Associated With Increased Carotid Intima-Media Thickness in Turkish Familial Mediterranean Fever Patients - Özlem GÜRBÜZ; Binnur BAĞCI; Can HÜZMELİ and Gökhan BAĞCI and Ferhan CANDAN (Archives of Rheumatology, 2016)
Objectives: This study aims to evaluate the carotid intima-media thickness (CIMT) in patients diagnosed with Familial Mediterranean fever (FMF) and investigate whether there is a relationship between glutathione-S-transferase (GST) gene polymorphisms and CIMT. Patients and methods: Sixty FMF patients (17 males, 43 females; mean age: 31.43±11.36 years; range 18 to 45 years) and 60 healthy controls (22 males, 38 females; mean age: 29.8±5.82 years; range 18 to 40 years) were enrolled in this study. Polymerase chain reaction-restriction fragment length polymorphism methods were carried out to assess GST polymorphisms. CIMT was measured by carotid ultrasonography. Biochemical parameters were also evaluated using biochemical methods. Results: Right and left CIMT of FMF patients were statistically significantly higher than that of control group (CIMT right p=0.001 and CIMT left: p=0.033). There was no significant association in terms of GST polymorphisms between FMF and control groups. No significant association was observed between GST polymorphisms and CIMT. Low density lipoprotein, erythrocyte sedimentation rate, and fibrinogen levels were significantly higher in the patient group (p<0.05). The difference between groups was not significant in terms of other biochemical parameters (p>0.05). Conclusion: Although no significant association was observed between GST polymorphisms and CIMT in FMF patients and controls, CIMT was statistically significantly higher in FMF patients compared to controls.